The Best of Technology Writing 2007 - Steven Levy, Editor (University of Michigan Press, 2007)
Together the essays in The Best of Technology Writing 2007 capture the versatility and verve of technology writing today. Solicited through an open online nominating process, these pieces explore a wide range of intriguing topics-from "crowdsourcing" to the online habits of urban moms to the digital future of movie production. The Best of Technology Writing 2007 will appeal to anyone who enjoys stellar writing.